Pilot label comprehension study for an over‐the‐counter combined oral contraceptive pill in the United States. Issue 1 (9th November 2022) - Grindlay, Kate; Key, Katherine; Bradford, Russell D.; Amato, Chiara; Blanchard, Kelly; Grossman, Daniel
Abstract: Context: A growing body of evidence supports over‐the‐counter access to oral contraceptives in the United States. An important consideration for over‐the‐counter approval is consumers' ability to understand key package label messages related to safety and effectiveness without clinician involvement. We developed a prototype over‐the‐counter Drug Facts Label for a combined oral contraceptive pill and conducted a pilot label comprehension study to evaluate consumer understanding of key messages for use. Methods: In November–December 2020, we conducted interviews with 163 adults and teens in the United States who were aged 12–49 years and identified as female or another gender but had a uterus and the ability to become pregnant. We developed 11 primary endpoints based on assessment of clinical risks that could occur if consumers fail to heed them, including messages about contraindications and directions for use; 11 secondary endpoints represented additional important information but with lower potential for clinical consequences if not understood. We evaluated endpoint comprehension by computing frequencies, percentages, and 2‐sided Exact (Clopper‐Pearson) 95% confidence intervals for observed proportions. Results: Ten of the 11 primary endpoints and 10 of the 11 secondary endpoints were each understood by ≥95% of participants. The remaining primary endpoint on use with prior blood clots was understood by 89% of participants. The remaining secondary endpoint on the product being designed for "people who have the ability to become pregnant" was understood by 83% of participants. Conclusion: Participants understood the key label information required for safe and effective combined oral contraceptive use without clinician involvement.